Photocrosslinked Microspheres: Rapid Production of Cell‐Laden Microspheres Using a Flexible Microfluidic Encapsulation Platform (Small 47/2019). Issue 47 (20th November 2019) - Seeto, Wen J.; Tian, Yuan; Pradhan, Shantanu; Kerscher, Petra; Lipke, Elizabeth A.
Abstract : In article number 1902058, Elizabeth A. Lipke and co‐workers report the establishment of a microfluidic encapsulation platform for rapid production of highly uniform cell‐laden hydrogel microspheres with high cell densities and a wide range of sizes. This new platform advances the ability to produce spheroidal engineered tissues for use in downstream applications including regenerative medicine.